Surface Functionalization of Gold Nanoparticles for Targeting the Tumor Microenvironment to Improve Antitumor Efficiency - Tan, Kin Fai; In, Lionel Lian Aun; Vijayaraj Kumar, Palanirajan (ACS applied bio materials, 2023)
Gold nanoparticles (AuNPs) have undergone significant research for their use in the treatment of cancer. Numerous researchers have established their potent antitumor properties, which have greatly impacted the treatment of cancer. AuNPs have been used in four primary anticancer treatment modalities, namely radiation, photothermal therapy, photodynamic therapy, and chemotherapy. However, the ability of AuNPs to destroy cancer is lacking and can even harm healthy cells without the right direction to transport them to the tumor microenvironment. Consequently, a suitable targeting technique is needed. Based on the distinct features of the human tumor microenvironment, this review discusses four different targeting strategies that target the four key features of the tumor microenvironment, including abnormal vasculature, overexpression of specific receptors, an acidic microenvironment, and a hypoxic microenvironment, to direct surface-functionalized AuNPs to the tumor microenvironment and increase antitumor efficacies. In addition, some current completed or ongoing clinical trials of AuNPs will also be discussed below to further reinforce the concept of using AuNPs in anticancer therapy.